The status of populations of some rare plants in the Almaty province, Enbekshikazakh district and their protection (Experimental biology, 2016)
The article presents data from a study of typical natural populations of Ferula iliensis, Ikonnikova kaufmanniana, Lіmonіum mіchelsonіі which grows special soil and climatic conditions in the Almaty province, Enbekshikazakh district (Mountains Boguty, Sugaty and Toraigyr).The studies were certain kinds of diversity, population structure of rare, endemic plants and age composition and abundance of this species in the studied populations. Our results indicate that they must take under the protection and in the future years to figure out the area of the populations of these species must be dealt with reintroduction.
Keywords: Ferula iliensis; Ikonnikovia kaufmanniana; Lіmonіum mіchelsonіі; species; endemic; relict; population.